Selection of sustainable suppliers in the oil and gas industry using fuzzy multi-criteria decision-making methods - Kittisak Jermsittiparsert (University of Novi Sad, Faculty of Technical Sciences, 2021)
Due to the globalization of competition in various fields, suppliers must have the best performance by creating different competitive advantages. In addition, the oil and gas industry has lots of sustainability issues in the supply phase. Accordingly, this study provides a comprehensive framework for ranking and selecting sustainable suppliers in the oil and gas industry. In this research, first, using the fuzzy analytical network process method, the indicators of selecting stable suppliers are ranked. Next, by applying the Electre method, the most appropriate suppliers are chosen. Numerical results show that the quality indicators of materials purchased from suppliers and commitment to contracts were ranked first and second among all criteria. Moreover, the efficiency of the proposed framework is approved by comparing with the real-world situation.